Autophagy, autophagy-associated adaptive immune responses and its role in hematologic malignancies - You, Liangshun (Oncotarget, 2016)
Autophagy is a tightly regulated catabolic process that leads to the degradation of cytoplasmatic components such as aggregated/misfolded proteins and organelles through the lysosomal machinery. Recent studies suggest that autophagy plays such a role in the context of the anti-tumor immune response, make it an attractive target for cancer immunotherapy. Defective autophagy in hematopoietic stem cells may contribute to the development of hematologic malignancies, including leukemia, myelodysplastic syndrome, and lymphoproliferative disorder. In blood cancer cells, autophagy can either result in chemoresistance or induce autophagic cell death that may act as immunogenic. Based on the successful experimental findings in vitro and in vivo, clinical trials of autophagy inhibitor such as hydroxychloroquine in combination with chemotherapy in patients with blood cancers are currently underway. However, autophagy inactivation might impair autophagy-triggered anticancer immunity, whereas induction of autophagy might become an effective immunotherapy. These aspects are discussed in this review together with a brief introduction to the autophagic molecular machinery and its roles in hematologic malignancies.